Antioxidant and Antimicrobial Screening of Endophytic Fungi Culture Filtrate from Purwoceng (Pimpinella alpina Molk) Leaf - Agustina L. N. Aminin; Nur Cahyanti; Alfina Sari; Nies Suci Mulyani; Bambang Cahyono (Jurnal Kimia Sains dan Aplikasi, 2020)
This is a preliminary study to determine the bioactivity potential of purwoceng leaf endophytic fungal metabolites. Endophytic fungi were isolated from purwoceng leaf and their secondary metabolite from culture filtrate were subjected to identify the antimicrobial, antioxidant, and phytochemical screening. The antioxidant activity was screened by scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH). The antimicrobial activity was screened using a good agar method toward Salmonella typhi, Escherichia coli, Bacillus subtilis, Staphylococcus aureus, dan Candida albicans. This study obtained five distinctive endophytic fungi isolates named A, B, C, D, and E. The endophytic fungal culture filtrate of C has the most extensive antimicrobial activity with phytochemical screening showing alkaloids, saponins, and terpenoids. The antioxidant potential of all culture filtrates seemed low because the DPPH amount was interfered with by pigment compounds. Culture filtrate of fungi A showed the highest antioxidant activity and contained phenolic and alkaloid compounds.